1996
DOI: 10.1097/00007632-199609150-00016
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Damping Measured With a Modified Pendulum Test in Patients With Fibromyalgia, Lumbago, and Cervical Syndrome

Abstract: The findings support the hypothesis that muscle tension in rheumatic patients results from overactivity of the sympathetic system (or part of it). Even in clinically localized pain syndromes, muscle damping is often increased in the legs. The test is valuable for quantitating muscle tension and the effectiveness of therapeutic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
4

Year Published

2000
2000
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 14 publications
1
17
0
4
Order By: Relevance
“…Moreover, the middle-aged FM subjects demonstrated a viscous stiffness of 1.2 times that of controls. The magnitude of ankle joint stiffness increase observed in this study is almost similar to the knee joint stiffness increase described by Wachter et al (1996) who also reported an increase of more than two times. The results indicate that the self-perceived stiffness increase of ankle reported by younger and middle-aged FM subjects is due to changes in elastic and/or viscous MA structures around the ankle.…”
Section: Fibromyalgia Subjects Have Significant Increase Of Ma Stiffnesssupporting
confidence: 90%
See 1 more Smart Citation
“…Moreover, the middle-aged FM subjects demonstrated a viscous stiffness of 1.2 times that of controls. The magnitude of ankle joint stiffness increase observed in this study is almost similar to the knee joint stiffness increase described by Wachter et al (1996) who also reported an increase of more than two times. The results indicate that the self-perceived stiffness increase of ankle reported by younger and middle-aged FM subjects is due to changes in elastic and/or viscous MA structures around the ankle.…”
Section: Fibromyalgia Subjects Have Significant Increase Of Ma Stiffnesssupporting
confidence: 90%
“…However, to date, very little attention has been placed on the quantitative measurement of the passive MA stiffness of a joint among FM subjects and the nature of stiffness increase (elastic and/or viscous) has not been yet determined. To our knowledge, only one team of researchers (Wachter et al 1996) showed an increase in knee joint stiffness in a small sample of 15 FM subjects.…”
Section: Introductionmentioning
confidence: 91%
“…Il est intéressant de remarquer qu'il existe une augmentation de la raideur musculaire élastique des chevilles des sujets fibromyalgiques malgré l'existence d'une raideur totale des chevilles équivalente dans les deux groupes. L'étude de Wachter et al [15] a quantifié la raideur musculaire des extenseurs des genoux de 15 sujets fibromyalgiques à l'aide d'un test du pendule modifié et n'arrive pas aux mêmes constatations. En effet, selon ces auteurs, la raideur musculaire totale au niveau des cuisses est plus importante chez les sujets fibromyalgiques que chez les sujets témoins.…”
Section: Discussionunclassified
“…En ce qui concerne la durée de l'atteinte, il est possible que notre échantillon de sujets jeunes ne nous ait pas permis de mettre en évidence une éventuelle modification de la raideur musculaire visqueuse et par voie de conséquence de la raideur musculaire « totale ». La durée de l'atteinte du syndrome de fibromyalgie était en moyenne de 15 mois pour notre échantillon et l'étude de Wachter et al [15] ne la précise pas.…”
Section: Discussionunclassified
See 1 more Smart Citation